Review of differentiated approaches to antiretroviral therapy distribution. Issue 8 (3rd August 2018) - Davis, Nicole; Kanagat, Natasha; Sharer, Melissa; Eagan, Sabrina; Pearson, Jennifer; Amanyeiwe, Ugochukwu "Ugo"
ABSTRACT: In response to global trends of maximizing the number of patients receiving antiretroviral therapy (ART), this review summarizes literature describing differentiated models of ART distribution at facility and community levels in order to highlight promising strategies and identify evidence gaps. Databases and gray literature were searched, yielding thirteen final articles on differentiated ART distribution models supporting stable adult patients. Of these, seven articles focused on distribution at facility level and six at community level. Findings suggest that differentiated models of ART distribution contribute to higher retention, lower attrition, and less loss to follow-up (LTFU). These models also reduced patient wait time, travel costs, and time lost from work for drug pick-up. Facility- and community-level ART distribution models have the potential to extend treatment availability, enable improved access and adherence among people living with HIV (PLHIV), and facilitate retention in treatment and care. Gaps remain in understanding the desirability of these models for PLHIV, and the need for more information the negative and positive impacts of stigma, and identifying models to reach traditionally marginalized groups such as key populations and youth. Replicating differentiated care so efforts can reach more PLHIV will be critical to scaling these approaches across varying contexts.